Utilization of Tofu Wastewater as a Fish Supplement: Impact on Fish and Economic Analysis - Aufa, Muhammad Azri; Utama, Gemilang Lara; Mansyur, Mansyur; Subhan, Ujang; Sukarman, Irwa Sukma bin (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2025)
Tofu liquid waste produced by the tofu industry in rural areas is often not reprocessed and has the potential to cause pollution if left untreated, so it is necessary to utilize tofu liquid waste which is the main idea in this research. The aim of this research is to analyze the potential for utilizing tofu liquid waste into fish supplements through the fermentation process with EM4 and Nitrobacter Plus and analyzing the economic and environmental benefits of utilizing tofu liquid waste into fish supplements. This research was conducted using an experimental method using a Completely Randomized Design (CRD) with 4 treatments and 3 replications. This research result showed that the provision of fish supplements from fermented tofu liquid waste has no significant effect on absolute weight growth, absolute length growth, specific growth rate, feed conversion ratio and survival rate. Based on the results of the economic analysis, the utilization of tofu liquid waste as a fish supplement was considered economically feasible with a Benefit Cost Ratio (BCR) of 1.285, Net Present Value (NPV) of Rp. 16,320,630,763 and Return on Investment (ROI) of 48.4%.